The social implications of applying alternative sanctions in The Punitive Policy of the United Arab Emirates: (Analytical study of theory) - Al-Zaabi, Omar Mohammed; Himat, Makia Gomaa Ahmed (Al-Adab Journal, 2022)
Penal policy varies from country to country in terms of the extent to which penalties imposed by the legislature are compatible with the values and customs of society, the extent to which sanctions achieve security and stability and the extent to which they need to be developed in order to keep pace with social, economic and religious developments.The problem with this research was the need to highlight the social effects of alternative sanctions, which have taken many forms, such as community service and electronic monitoring, in terms of both positive and negative impacts.The importance of the study lies in the fact that, although penitentiary institutions are developed and apply the most modern reform and rehabilitation systems, they are not in keeping with many short-term sentences of deprivation of liberty, and they have shown their negative results as a result of their application.Consequently, alternatives to these sentences must be applied in order to protect the families of convicts and society.The results of the study showed that the application of alternative penalties had proved to be remarkably successful, despite the fact that in some cases they were not compatible with the objective of punishment in both the private and general deterrence aspects, such as repeat offenders and criminal recidivists.The proposals and recommendations noted that attempts should be made to apply alternative penalties to certain other penalties involving deprivation of liberty for a long period of time, which enjoy good conduct and conduct and the purity of their criminal record.